1999
DOI: 10.1097/00126334-199910010-00010
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Non-B Subtypes in Newly Diagnosed HIV-1 Infections in Switzerland

Abstract: HIV-1 subtypes were determined in newly diagnosed residents of Switzerland. Blood was anonymously collected from patients with a first confirmed positive HIV-1 test result. Viral DNA from the env V3-V5 region was amplified by nested polymerase chain reaction (PCR) and screened for subtype B by heteroduplex mobility assay. All amplicons not identified as B were sequenced. From November 1996 to February 1998, 206 samples were analyzed. Main transmission risks were unprotected heterosexual (55.7%) or homosexual (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…Like other European countries, Switzerland has a high rate of non-B infections [30] and the proportion of such viruses among newly diagnosed HIV-1 infections has now reached proportions of two-thirds in women and one-third in men (unpublished data from the Swiss genotypic resistance test database). Patients infected with such viruses may produce antibodies of reduced avidity to the subtype B antigens frequently employed in diagnostic tests, thus leading to low-reactivity patterns when tested and subsequent false diagnosis of recent infections.…”
Section: Discussionmentioning
confidence: 99%
“…Like other European countries, Switzerland has a high rate of non-B infections [30] and the proportion of such viruses among newly diagnosed HIV-1 infections has now reached proportions of two-thirds in women and one-third in men (unpublished data from the Swiss genotypic resistance test database). Patients infected with such viruses may produce antibodies of reduced avidity to the subtype B antigens frequently employed in diagnostic tests, thus leading to low-reactivity patterns when tested and subsequent false diagnosis of recent infections.…”
Section: Discussionmentioning
confidence: 99%
“…Subtype B dominates the Swiss HIV-1 epidemic [10, 11], and we therefore focused on this subtype ( n  = 9,157 sequences). Because antiretroviral therapy strongly distorts viral diversity [12], we included only sequences from patients who were therapy-naïve at the time of sampling and for whom an independent estimate of infection time was available (3,307 sequences, each from a different patient).…”
Section: Methodsmentioning
confidence: 99%
“…Subtype B predominates in the Americas, Europe, Japan, and Australia, whereas non-B subtypes predominate in Africa and in most Asian countries. Many studies have reported an increasing prevalence of non-B subtypes in Europe since the beginning of the epidemic (2)(3)(4)(5)(6)(7)(8)(9)(10). Whereas there is a common notion that HIV-1 infections with non-B subtypes are mainly associated with migrant populations from the developing world, there is increasing evidence that the epidemiology of non-B viruses in Europe results from both migration and domestic transmissions (11)(12)(13).…”
mentioning
confidence: 99%
“…Whereas there is a common notion that HIV-1 infections with non-B subtypes are mainly associated with migrant populations from the developing world, there is increasing evidence that the epidemiology of non-B viruses in Europe results from both migration and domestic transmissions (11)(12)(13). Most of the studies have described the increasing prevalence of non-B variants in Europe among newly diagnosed HIV-1 infections or patients referred for antiretroviral resistance testing (4,(6)(7)(8)(9). However, the duration of infection for each new diagnosis was frequently unknown in these studies.…”
mentioning
confidence: 99%